(untitled) (REVISTA DE HUMANIDADES Y CIENCIAS SOCIALES Y MULTIDISCIPLINARIA, 2021)
The investigation of market in international level, competitive conditions, small relatively cycle of products, more increased requirements of clients, political and economic developments and continuous technological development consist samples of the influential agents in taking decisions marketing as a result the development of science information with equipment level but also software so the changing conditions of business environment give new dimensions in operation of taking decisions in marketing. The use of internet offers an essential help in the direction of a better understanding and successful management of dangers that the professional engagement in enterprises that maintain or intend to transfer a part or the total of their activities to internet buying sites involves. Τhe specific article in order to investigate of factors influence internet in environment of marketing, the causes of activity internet in markets based on method of secondary research which used for the collection data which collected from libraries, sources and data from the same enterprises for the creation of basis bibliographic review. Followed the content analysis, export conclusions for the use products from consumers and understanding results of the actions marketing. The main target of article is researching the influence of internet in action of entrepreneurship.